Anemia on Chronic Kidney Disease: The Role of Hypoxia-Inducible Factor Prolyl Hydroxylase Inhibitors - Ni Wayan Anantika Riani; I Gde Raka Widiana (Intisari Sains Medis, 2022)
Anemia is one of the homeostatic abnormalities caused by chronic kidney disease and also frequently problem encountered in end-stage renal disease patients, regardless of the hemodialysis treatment. Anemia in chronic kidney disease significantly impairs kidney function, increases morbidity and mortality risk, and deteriorates the quality of life. Chronic kidney disease’s patients with anemia conditions are affected by numerous factors, including decreased production of endogenous erythropoietin, functional and absolute iron deficiency, and elevated hepcidin levels due to inflammation, particularly in hemodialysis patients. Treatment options for anemia in chronic kidney disease include exogenous erythropoietin and iron supplementation. A new mechanism known as the "hypoxia-sensing system" termed a mediator of erythropoietin synthesis, has been proposed to boost endogenous erythropoietin synthesis. The hypoxia-inducible factor activates specific gene expression and contributes to a physiological response to lower tissue oxygen levels. Chronic kidney disease’s patients who are contraindicated or are hyporesponsive to therapy with erythropoiesis-stimulating drugs may utilize this mechanism as an alternative.